Efektivitas Penggunaan Blanket Warmer untuk Pencegahan Hipotermi pada Pasien Post-Operative dengan Pengaruh Anastesi Spinal - Annisa Ranti Nur Azizah; Fahni Haris; Rahmawanto (TRIAGE Jurnal Ilmu Keperawatan, 2025)
Background: Postoperative hypothermia is a common complication frequently occurring in patients undergoing spinal anesthesia. This condition can delay recovery, increase the risk of wound infection, and prolong the length of hospital stay. One method used to maintain the patient's body temperature is the use of a blanket warmer. Objective: To determine the effectiveness of blanket warmer usage in preventing hypothermia in postoperative patients undergoing spinal anesthesia. Methods: This study employed a case study design with a one-group pretest-posttest approach without a control group. The sample consisted of 12 postoperative patients in the Recovery Room of RSUD dr. Tjitrowardojo Purworejo. The patients underwent surgical procedures with spinal anesthesia. The intervention group received blanket warmer therapy for 10 minutes during the postoperative recovery phase. Body temperature was measured before and after the intervention using an axillary thermometer for one minute. Results: The use of a blanket warmer demonstrated a significant increase in patients' body temperature before and after the intervention (p= 0.001, p<0.05). The majority of patients in the intervention group successfully maintained a mean body temperature of 36.32°C. Conclusion: Blanket warmers are effective in preventing hypothermia in postoperative patients undergoing spinal anesthesia. The use of this device is recommended as part of the standard postoperative care to enhance patient comfort and safety.